Capillary Microhematocrit Measurement as a Screening Test for Anemia in Children - Mustaring, Mustaring; Tranggana, Sunar; Daud, Dasril (Paediatrica Indonesiana, 1990)
The spectrophotometric measurement of hemoglobin performed with a well standardized instrument using venous blood is widely accepted as a reference standard for anemia. In developed countries automated electronic counters are used instead However, this method of determining anemia is not practical for screening in developing countries as it requires special skill or expensive equipment to obtain the specimen or to perform the test. The primary objective of this study was to determine the feasitnlity of ustng capillary nucrohematoerit measurement as a screening test for anemia. The 104 patients examined ranged in age from 6 months to 6 years; 65 were males and 36 females Sixty one of the 104 cases (58.7%) were below 2 years of age and the other 43 cases (41.5%) were older than 2 years Hemoglobin values ranged from 2.7-13.5 g/dl and capillary microhematocrit ranged from 9-41%. Analysis of the result showed a significant correlation between the capillary microhematocrit values and the capillary hemoglobin values (r = 0.99 and p < 0.001) The sensitivity of the microhematocrit method for detecting anemia was 91.11% and the spectficity was 89.83%. The predictive value for a normal (negative) microhematocrit was 92.98% and the predictive value for a low (positive) microhematocrit was 87.23%. We conclude from this study that the capillary microhematocrit measurement method can be appropriately used as a screening test for anemia.